Analisis Penerimaan Aplikasi Website Dengan Menggunakan TECHNOLOGY ACCEPTANCE MODEL 2(TAM 2) Pada Raja Duren - Hardjito, Faisal Rachman; Sulistiowati, Sulistiowati; Binawati, Lilis (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
Raja Duren has an official website that addressed in www.rajaduren.co.id as a source of information from a wide variety of food products and beverages. Such information includes promotions available at Raja Duren, location, photos of food and drinks, the vision and mission as well as other information about Raja Duren. In this study, an analysis of application acceptance website using technology acceptance model 2 (TAM 2) at Raja Duren. The data collection is done by giving a questionnaire offline using sampling methods unknown population survey questionnaires were distributed as many as 120 people. Data were analyzed using AMOS SEM applications. This research led to the conclusion that subjetive norm does not affect the intention to use the website Raja Duren. Subjective norm, job relevance and Image no significant effect on perceived usefulness on the website Raja Duren. Subjective norm no significant effect on the image on the website Raja Duren. Result demonstrability output quality and significant effect on perceived usefulness on the website Raja Duren. Perceived ease of use does not significantly influence the perceived usefulness on the website Raja Duren. Perceived usefulness significantly influence the intention to use the website Raja Duren. Perceived ease of use significantly influence the intention to use the website Raja Duren. Intention to use a significant effect on usage behavior on the website Raja Duren.